Comparative Toxicity of Neem and Seven Insecticides on Hazelnut Weevil (Curculio nucum Col.: Curculionidae) with Laboratory Bioassays - TUNCER, CELAL; SARUHAN, ISLAM; AKCA, IZZET (Asian Journal of Chemistry, 2010)
Hazelnut weevil (Curculio nucum L. Col., Curculionidae) is common pest in hazelnut (Corylus avellanae) and insecticides are the primary tool used to manage infestation of it. The insecticides are applied for its control for many years; therefore, to evaluate their effectiveness and establishing baseline insecticide mortality for future resistance monitoring programs are needed. In this study, efficacy of 7 insecticides including benfurocarb, carbaryl, carbosulfan, furathiocarb, lambda-cyhalothrin, methiocarb and 1 botanical pesticide with azadirachtin were evaluated in laboratory bioassays and lethal concentrations were determined against hazelnut weevil. There was no acute toxicity of azadirachtin on hazelnut weevil in 72 h. The highest toxicity based on LC50 values was observed in lambda-cyhalothrin (3.06 mg AI/L) and followed by carbosulfan (12.4 mg AI/L). The LC50's (mg AI/L) for furathiocarb, methiocarb and benfurocarb in residual filter paper method were 36, 44.5 and 90.2, respectively. The least efficacy were determined in carbaryl, LC50's were 224.3 and 277.5 mg AI/L for two carbaryl preparations. The lowest slopes of probit lines were determined for carbaryl whereas it was steepest for carbosulfan. LC99's were close or upper than recommended field doses in carbaryl while they were lower for other compounds.